Rekonstruksi Kaidah Amr dalam Ushul Fiqh terhadap kewajiban perpajakan dalam perspektif hukum positif di Indonesia - Ziankha, Nazwa Ayudya (Maliki Interdisciplinary Journal, 2026)
This study examines the reconstruction of the amr principle in Islamic legal theory (ushul fiqh) toward tax obligations within the perspective of positive law in Indonesia. The main issue addressed in this research is the perception among some Muslim communities that taxation lacks normative legitimacy in Islamic law and is considered contradictory to the obligation of zakat. This research employs a normative-juridical approach using descriptive and comparative analysis methods between the theory of amr in ushul fiqh and Indonesian tax regulations. The data sources were obtained from classical and contemporary ushul fiqh literature, statutory regulations, and relevant academic studies. The findings indicate that the principle of al-ashl fi al-amr li al-wujub can serve as a foundation for understanding tax obligations as binding commands issued by the government as ulil amri (legitimate authority). Tax obligations are also in line with the principles of maqashid al-shari’ah because they aim to achieve public welfare, maintain economic stability, and support national development. Therefore, taxation obligations not only possess constitutional legitimacy within Indonesian positive law but can also be accepted within the framework of Islamic law through a contextual and integrative ushul fiqh approach.